The Relationship Between Water Scarcity, Climate Change, and Mental Health: A Systematic Review - İlknur Taşkıran; Hatice Sinem Şenli; Begüm Arıtan (Clinical Journal of Health Sciences, 2026)
The aim of this study is to examine the relationship between water scarcity, climate change, and mental health through a systematic review. Water scarcity is defined as the long-term inadequate management of available water resources and the failure to meet increasing demand; climate change, in turn, is a fundamental driver that both accelerates and deepens this scarcity through drought, heat waves, and disruptions to the water regime. In recent years, it has increasingly been emphasized that these environmental pressures affect not only physical health but also mental health through outcomes such as depression, anxiety, post-traumatic stress, suicide, eco-anxiety, and ecological grief. The review was planned and reported in accordance with the PRISMA 2020 statement. Searches were conducted in Turkish and English across national and international academic databases, primarily Google Scholar, using the keywords “water scarcity,” “climate change,” “drought,” “mental health,” and “eco-anxiety.” Of the 74 records identified, 44 studies were included after removing duplicates and completing a two-stage screening process. The methodological quality of the empirical studies was appraised using criteria from the Mixed Methods Appraisal Tool (MMAT), and the findings were analyzed using thematic synthesis. The synthesis yielded five analytical themes: the direct effects of climate change and drought on mental health, water insecurity and psychosocial distress, drought-related economic loss and suicide risk, eco-anxiety–solastalgia–ecological grief, and protective factors including adaptation, community resilience, and mental health policies. The findings indicate that drought and water insecurity increase depression, anxiety, and psychological distress; elevate suicide risk through economic devastation and forced migration; and give rise to novel mental health responses such as eco-anxiety and ecological grief associated with environmental loss. Community resilience, social support, adaptation policies, and access to mental health services emerge as protective factors that moderate these risks. In conclusion, water scarcity and climate change should be addressed not only as environmental and physical problems but also as a priority mental health issue. Integrating the mental health dimension into climate adaptation and water security policies, strengthening psychosocial support mechanisms for vulnerable groups, and raising public awareness are critical to mitigating these effects.